Presidential Power’s Limitation to Emergency Provisions in Indonesia - Jayus Jayus; Muhammad Bahrul Ulum (Jurnal Cita Hukum, 2020)
Abstract.After the demise of Suharto’s regime, Indonesia’s 1945 Constitution was successfully revised from 1999 to 2002. This period of constitutional revision added emphasis to avoid authoritarian administrations such as those experienced during the times of Sukarno and Suharto; consequently, the constitution was re-designed to limit the powers of the government. This article examines the trajectory of constitutional practices in the post-constitutional revision by taking into account emergency provisions exemplifying the new challenges of democratization in contemporary Indonesia. Currently, emergency provisions are amongst the unamended norms in the 1999-2002 agenda of constitutional revision. As a consequence, authoritarianism threatens the future of liberal democracy in Indonesia, especially the enjoyment of civil and political rights. Hence, this analysis elucidates the extent to which the deficit is inherent to Indonesia’s revised constitution on emergency laws and how this deficit threatens the design of liberal constitutionalism. Selected cases were collected to illustrate how Indonesia’s current constitution is reflected, articulated, debated, and negotiated toward the idea of legally limited powers. The deficits have resulted in two major adverse impacts; first, the ambiguous provisions on emergency laws prevail as they are mentioned in Articles 12 and 22 of the 1945 Constitution; second, the President’s monopoly on the power to issue emergency laws is a result of the absence of limitations outlined in the constitution. While the monopoly of such a power is often utilized by the government under the backdrop of constitutional legitimacy, there is a possible effort to eschew potential authoritarianism to add the constitutional restraint to presidential powers in the agenda of constitutional revision.Keywords: constitutionalism, emergency provisions, Indonesian constitution Batasan Kekuasaan Presiden untuk Ketentuan Darurat di IndonesiaAbstrak.Pasca runtuhnya rezim Suharto, UUD 1945 berhasil direvisi dari 1999 hingga 2002. Revisi konstitusi periode ini menambahkan penekanan untuk menghindari pemerintahan otoriter seperti yang dialami pada masa Sukarno dan Suharto; akibatnya, konstitusi dirancang ulang untuk membatasi kekuasaan pemerintah. Artikel ini mengkaji lintasan praktik ketatanegaraan dalam revisi pasca konstitusi dengan memperhatikan ketentuan darurat yang menjadi contoh tantangan baru demokratisasi di Indonesia kontemporer. Saat ini, ketentuan darurat merupakan salah satu norma yang belum diamandemen dalam agenda revisi konstitusi 1999-2002. Akibatnya, otoritarianisme mengancam masa depan demokrasi liberal di Indonesia, khususnya penikmatan hak sipil dan politik. Oleh karena itu, analisis ini menjelaskan sejauh mana defisit melekat pada revisi konstitusi Indonesia tentang undang-undang darurat dan bagaimana defisit ini mengancam rancangan konstitusionalisme liberal. Kasus-kasus terpilih dikumpulkan untuk menggambarkan bagaimana konstitusi Indonesia saat ini direfleksikan, diartikulasikan, diperdebatkan, dan dinegosiasikan menuju gagasan kekuasaan terbatas secara hukum. Defisit tersebut mengakibatkan dua dampak merugikan yang besar; pertama, ketentuan hukum darurat yang ambigu sebagaimana diatur dalam Pasal 12 dan 22 UUD 1945; kedua, monopoli Presiden atas kewenangan mengeluarkan undang-undang darurat adalah akibat tidak adanya batasan yang diuraikan dalam konstitusi.Kata kunci: konstitusionalisme, ketentuan darurat, konstitusi Indonesia Аннотация.После падения режима Сухарто  Конституция 1945 года была успешно пересмотрена с 1999 по 2002 год. Пересмотр конституции на этот период добавил напряжение на недопущение авторитарного правления, которое имело место в периоды Сукарно и Сухарто; в результате конституция была изменена с целью ограничить полномочия правительства. В данной статье исследуется развитие конституционной практики в период постконституционного пересмотра с учетом чрезвычайных положений, которые стали примерами новых вызовов демократизации в современной Индонезии. В настоящее время чрезвычайные положения являются одной из неизменных норм в программе пересмотра конституции на 1999–2002 года. В результате авторитаризм угрожает будущему либеральной демократии в Индонезии, особенно осуществлению гражданских и политических прав. Таким образом, этот анализ объясняет, в какой степени недостатки связаны с пересмотром конституции Индонезии о чрезвычайном законе, и как эти недостатки угрожают проекту либерального конституционализма. Отобранные случаи собраны, чтобы проиллюстрировать, как текущая конституция Индонезии отражается, формулируется и обсуждается в отношении понятия юридически ограниченной власти. Этот дефицит привёл к двум основным пагубным эффектам: во-первых, неоднозначные положения чрезвычайного закона, предусмотренные статьями 12 и 22 Конституции 1945 года; во-вторых, монополия президента на право издавать чрезвычайные законы является результатом отсутствия каких-либо ограничений, предусмотренных конституцией.Ключевые слова: конституционализм, чрезвычайные положения, конституция Индонезии.